Comparison of cognitive function between early- and late-onset late-life depression in remission. (August 2020) - Cheng, Ying-Chih; Liu, Shen-Ing; Chen, Chun-Hsin; Liu, Hsing-Cheng; Lu, Mong-Liang; Chang, Ching-Jui; Chiu, Wei-Che; Sun, I-Wen; Yao, Lin-Sheng; Chiu, Chih-Chiang; Robert, Stewart
Highlights: In people with late-life depression, there were no significant difference in overall cognitive composite scores in euthymic older people between those with early- (EOD) and late-onset (LOD) depression. Immediate recall scores were lower in participants with EOD after adjustment for possible confounders. Abstract: Differences in cognitive function have been suggested in people with late-life depression between those with early- (EOD) and late-onset (LOD), possibly reflecting different etiologies. The cutoff point for EOD and LOD was the first depressive episode before age 60 or later. However, depressive symptoms at the time of disorder are important confounders. The study aimed to compare cognitive function in older people with EOD and LOD in the euthymic state. A sample of 135 participants aged 60+ with a history of major depressive disorder in remission, received neuropsychological evaluation including tests of memory, attention, processing speed, visuospatial function, language, and executive function. Individual test scores and a derived composite score were investigated as dependent variables against age of onset using multiple linear regressions adjusted for potential confounders, including residual depressive symptoms. We found EOD (N = 67) and LOD (N = 68) groups did not differ significantly in overall composite cognitive scores after adjustment. Of individual test scores, only those for immediate recall were significantly lower in participants with EOD compared to LOD. In conclusion, the study found no associations between cognitive function and age of onset in this sample of people with depressive disorder in remission. Active or residual depressive symptoms might have confounded this relationship in previous research.